Toward net 0: Digital CO₂ proofs for the sustainable transformation of the European economy - Christina Leinauer; Marc-Fabian Körner; Jens Strüker (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2023)
As the decarbonization of industry has become an increasing priority, so has the need for emissions data and the requirement for cross-sector emissions reporting. What challenges and opportunities does industry face? How can digital solutions help leverage the potential of climate-friendly products in emerging climate-neutral lead markets? Based on interviews with experts from various industries, our study with Fraunhofer-FIT "Towards net 0: Digital CO2 proofs for the sustainable transformation of the European economy" presents hurdles and digital solutions as well as conclusions for policy makers. The study comes to the conclusion that granular, secure CO2 proofs on the one hand offer a possibility to manage the increasing effort for the collection, processing and provision of CO2 information more efficiently and at the same time can accelerate and simplify the transition to climate-neutral production processes and products.
urn:nbn:de:bvb:703-epub-6827-4
Keywords: 650